The Effect of Self-Regulation on Social Emotional Skills in Early Childhood - Sitinjak, Mika; Puridawaty, Brigita (Pusat Penerbitan Universitas (P2U) Unisba, 2024)
This study was conducted to determine the effect of self-regulation on the social-emotional abilities of group B children at PT’s Kindergarten. The type of research used is quantitative research with a correlational approach, or non-experimental research, which is almost the same as ex facto research. This study used a sample of 20 children in group B. The instrument used was a questionnaire, while the data analysis in this study used SPSS 22. Based on the results of the study, it was shown that there was an influence of self-regulation on the social-emotional abilities of Group B children at PT’s Kindergarten. With a significance value (Sig.) of 0.000 less than a probability of 0.05, it can be concluded that H0 is rejected and Ha is accepted, which means that